Effect of incident hepatitis C infection on CD4+ cell count and HIV RNA trajectories based on a multinational HIV seroconversion cohort - Van Santen, D; Van Der Helm, J; Touloumi, G; Pantazis, N; Muga, R; Gunsenheimer-Bartmeyer, B; Gill, M; Sanders, E; Kelleher, A; Zangerle, R; Porter, K; Prins, M; et al. (Wolters Kluwer Health, 2019)
Background: Most studies on hepatitis C virus (HCV)/HIV-coinfection do not account for the order and duration of these two infections. We aimed to assess the effect of incident HCV infection, and its timing relative to HIV seroconversion (HIVsc) in HIV-positive MSM on their subsequent CD4+ T-cell count and HIV RNA viral load trajectories. Methods: We included MSM with well estimated dates of HIVsc from 17 cohorts within the CASCADE Collaboration. HCV-coinfected MSM were matched to as many HIV monoinfected MSM as possible by HIV-infection duration and combination antiretroviral therapy (cART) use. We used multilevel random-effects models stratified by cART use to assess differences in CD4+ cell count and HIV RNA viral load trajectories by HCV-coinfection status. Findings: We matched 214 (ART-naive) and 147 (on cART) HCV-coinfected MSM to 5384 and 3954, respectively, matched controls. The timing of HCV seroconversion (HCVsc) relative to HIVsc had no demonstrable effect on HIV RNA viral load or CD4+ cell count trajectories. In the first 2–3 years following HCVsc CD4+ cell counts were lower among HCV-coinfected MSM, but became comparable with HIV monoinfected MSM thereafter. In ART-naive MSM, during the first 2 years after HCVsc, HIV RNA viral load levels were lower or comparable with HIV monoinfected, tending to be higher thereafter. In MSM on cART, HCV had no significant effect on having a detectable HIV RNA viral load. Interpretation: Irrespective of the duration of HIV infection when HCV is acquired, CD4+ cell counts were temporarily lower following HCVsc, even when on cART. The clinical implications of our findings remain to be further elucidated.